Evolution of concepts regarding the duration of the construction process: from regulatory approaches to integrated project planning models - BLONNYI, Andriy (Ways to Improve Construction Efficiency, 2025)
The evolution of concepts regarding the duration of the construction process reflects a profound transformation in project management approaches under dynamic market conditions. From rigidly regulated normative systems, where time was viewed as a fixed constant, the construction industry has transitioned to integrated models that consider the multifactorial, uncertain, and stochastic nature of temporal processes. Early approaches were based on standardized indicators focused on unified conditions for performing work; however, practical experience demonstrated their limitations due to the underestimation of external influencing factors. With the advancement of analytical and digital technologies, duration began to be perceived as a dynamic indicator of managerial system efficiency. Models emerged that account for the interdependence of time, resources, and financial indicators, as well as the system’s ability to respond to deviations. A particularly significant role in this evolution was played by network methods – CPM and PERT – which laid the foundation for the critical path principle. The subsequent development of stochastic and fuzzy models made it possible to treat time not as a rigid constraint but as a variable management resource. In the digital era, the concept of duration is integrated with BIM modeling, KPI indicators, and analytical platforms that enable scenario planning, risk forecasting, and real-time schedule management. As a result, time ceases to be a passive element of control and transforms into an active management tool that ensures system flexibility and adaptability. Project duration is now regarded as the outcome of the interaction between technological, organizational, economic, and behavioral factors that determine the overall resilience of the construction process. In modern management, it becomes a criterion of enterprise maturity, reflecting not only the pace of task execution but also the quality of decision-making, communication efficiency, responsiveness to change, and the degree of digital integration. Thus, the current interpretation of duration in construction has shifted from a purely calendar-based perspective to a system-analytical one, where time is viewed as a strategic asset capable of enhancing enterprise competitiveness, ensuring project resilience, and supporting continuous industry development. The evolution of approaches to duration management demonstrates that the future of construction lies in the creation of adaptive, digitally driven systems in which duration becomes a key parameter of strategic planning, fully integrated into the overall architecture of project management.